Primary antiphospholipid syndrome in pediatrics: beyond thrombosis. Report of 32 cases and review of the evidence - Alfonso-Ragnar Torres-Jimenez; Virginia Ramirez-Nova; Adriana Ivonne Cespedes-Cruz; Berenice Sanchez-Jara; Alejandra Velazquez-Cruz; Vilma Carolina Bekker-Méndez; Francisco Xavier Guerra-Castillo (Pediatric Rheumatology Online Journal, 2022)
Abstract Objective Describe the frequency of thrombotic and non-thrombotic clinical manifestations, laboratory, treatment and prognosis in patients with pediatric primary antiphospholipid syndrome. Material and methods A retrospective study was carried out in patients with a diagnosis of primary antiphospholipid antibody syndrome, under 16 years of age, under follow-up by the pediatric rheumatology service of the General Hospital, National Medical Center, La Raza, from January 2013 to December 2020. The antiphospholipid syndrome was defined when it met the laboratory criteria of the Sidney criteria and the presence of thrombosis or non-criteria manifestations of the disease (hematological, neurological, cutaneous, renal, cardiac or pulmonary). Demographic, clinical, laboratory, treatment, and prognosis data were collected. Results We report 32 patients, 21 female (65%) and 11 male (35%), mean age 11.75 years, evolution time 16 weeks. Thrombosis 9 patients (28%), 1 arterial and 8 venous. Non-thrombotic manifestations; Hematologic: thrombocytopenia 22 patients (69%), autoimmune hemolytic anemia 13 (40%), Fisher-Evans syndrome 6 (19%), lupus anticoagulant with hypoprothrombinemia syndrome 2 (6%). Dermatological: livedo reticularis 20 (62%), skin ulcers 2 (6%), Raynaud's phenomenon 8 (25%). Neurological: epilepsy 1 (3%), migraine 3 (9%), chorea 1 (3%) and cognitive impairment 3 (9%). Renal in 4 (13%). Laboratory: prolonged aPTT 30 (93%), lupus anticoagulant 32 (100%), positive IgG anticardiolipin 20 (62%), positive IgM anticardiolipin 19 (60%). AntiB2GPI was performed in only 3 patients, being positive in all. Treatment: anticoagulation in patients with thrombosis, antiplatelet in 23 (72%), steroid 30 (94%), immunosuppressant 30 (94%) and rituximab 4 (12.5%). No deaths were reported. Conclusions The clinical characteristics of patients with pediatric primary antiphospholipid syndrome differ from those presented in adults, since non-thrombotic manifestations are more frequent in children, for which classification criteria that include these manifestations are necessary for a better characterization of the disease in pediatric population.